Isolation And Characterization Of A Molybdenum-Reducing, Phenol- And Catechol-Degrading Pseudomonas Putida Strain Amr-12 In Soils From Egypt - AbdEl-Mongy, MA; Shukor, MS; Hussein, S; Ling, APK; Shamaan, NA; Shukor, MY (Vasile Alecsandri Univ Bacau, 2024)
Indexed by WOS